Gastrointestinal Stromal Tumors: A Single Institution Experience of 176 Surgical Patients. Issue 7 (July 2013) - Fisher, Sarah B.; Kim, Steven C.; Kooby, David A.; Cardona, Kenneth; Russell, Maria C.; Delman, Keith A.; Staley, Charles A.; Maithel, Shishir K.
Large single-institution series of patients undergoing resection for gastrointestinal stromal tumors (GIST) are lacking. Clinicopathologic characteristics and postoperative outcomes were retrospectively collected and analyzed from patients undergoing resection for GIST from 2002 to 2011. One hundred seventy-six patients were identified; 156 underwent resection of primary nonmetastatic disease. KIT mutations were identified in 131 patients (84.0%). Of the 156 patients with primary disease, the most common site was the stomach (75.6%). Tumors were categorized as very low (24.4%), low (35.9%), intermediate (12.2%), high (24.4%), or unknown (3.2%) risk. Symptomatic patients more often had high risk (35.6 vs 9.8%; P < 0.0001) and larger tumors (7.3 vs 3.0 cm; P < 0.0001). Forty-seven patients (30.1%) underwent laparoscopic resection (LR). Compared with open surgery, LR was performed for smaller tumors (3.8 vs 6.2 cm; P = 0.002). Positive margin rates were similar (4.3% LR vs 10.2% open; P = 0.346). Median follow-up for the 156 patients with primary tumors was 32.9 months; mean overall survival was 120.9 months (median not reached). Of the 20 patients with metastatic GIST (excluded from above analysis), five patients (25.0%) died of disease with a median follow-up of 15.9 months. Most patients with resectable primary GIST have a favorable prognosis. The presence of symptoms directly related to GIST may be associated with a poor prognosis and is likely related to increased tumor size. Laparoscopic resection is well tolerated and does not appear to compromise outcomes in well-selected patients. Highly selected patients with metastatic disease may benefit from resection.